Pengenalan Konsep Dasar-Dasar Kepemimpinan (Leadership) Bagi Pengurus OSIS di SMA Negeri 11 Jakarta Timur - Maris Agung Triandewo; Ida Farida (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
One of the efforts to develop and identify leadership skills of Student Council Administrators (OSIS) of SMA 11 East Jakarta is to provide training of the basics of leadership. This training is very relevant for them considering their position as student council administrators which is directly related to leadership skills in daily life at school. The main core of the training is the introduction of old and new leadership paradigms and the differences between managers and leaders. It is hoped that with the training, OSIS Administrators of SMA 11 Jakarta will gain additional insight on leadership that can be implemented in organizational life both now and at the higher education level in the future.